Overwhelming sepsis presenting as sudden unexpected death. Issue 3 (September 1993) - Sharief, N; Khan, K; Conlan, P
Abstract : Four children, including three infants, who died suddenly and unexpectedly are described. In three of the cases group A beta haemolytic streptococcus was cultured and in the fourth Streptococcus pneumoniae. The organism was grown from multiple sites including blood in two of them. Without microbiological investigation the diagnosis would have been sudden unexpected death syndrome.